HUBUNGAN BEBAN KERJA DENGAN KINERJA PERAWAT DALAM MENGIMPLEMENTASIKAN PATIENT SAFETY DI RUMAH SAKIT STELLA MARIS MAKASSAR: RELATIONSHIP BETWEEN WORK LOADS AND NURSING PERFORMANCE IN IMPLEMENTING SAFETY PATIENT IN STELLA MARIS MAKASSAR HOSPITAL - Beda, Nikodemus Sili; Komariah, Euis Dedeh; Anggriani, Elni; Feramita, Bettoen Talumba (Stikes Wira Medika Bali, 2019)
Patient safety in a hospital is often associated with work loads problem due to lack of available staff / nurses. The purpose of this study was to determine the workload and its relationship with work achievement of nurses at Stella Maris Hospital Makassar. The research design used was an observational analytic with cross-sectional. The sample size were 80 respondents with probability sampling techniques using random sampling. The instrument used was a questionnaire. The results of the study obtained that 59 respondents (73.8%) worked more and as many as 62 (77.6%) had good performance. From the results of the chi square test obtained p value = 0.004, which showed the value of p <α that is α = 0.05 so that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. So, there was correlation between workload and nursing performance in implementing the Patient Safety at Stella Maris Hospital Makassar. Then it can be concluded that nurses have a longer workload.